A Retrospective Analysis of Employee Education Level on Weight Loss Following Participation in an Online, Corporately Sponsored, Weight Loss Program. Issue 10 (October 2020) - Earnest, Conrad P.; Church, Timothy S.
Abstract : Objective: To examine weight loss characteristics relative to education for employees participating in an online weight loss program. Methods: We examined percent weight loss (primary outcome), the achievement of clinical cut-points (secondary outcome) by class attendance, and education strata (High School and Trade through Post-Graduate). Results: Overall, the pooled cohort lost a significant percentage of their starting weight (–2.05%, 95% CI, –2.07, –2.04). Women (–1.95%, 95% CI, –1.97, –1.94) lost significantly less than men (–2.38%, 95% CI, –2.141, –2.35). Those attending less than or equal to seven classes lost significantly less weight (0.75% [95% CI, –0.77, –0.74] vs more than or equal to eight classes attendees [–3.50%, 95% CI, –3.52, –3.48]). Class attendance was significantly correlated to weight loss ( r  = 0.57, P  < 0.001) and was consistent across education strata. Conclusions: Online weight loss programming is effective across education strata and class participation is essential to participant success.